OPTIMALISASI PENGGUNAAN FAKTOR PRODUKSI USAHATANI KOPI DI BAWAH TEGAKAN PINUS (Pinus merkusii) - Suhartono Suhartono; Ary Widiyanto (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2020)
Efforts to increase land productivity in forest areas have been carried out through community-based forest management programs in the form of coffee planting activities under pine stands. However, the coffee productivity produced by farmers is still considered not optimal, even though farmers have allocated all factors of production in their farming processes. This study aims to determine the scale of business and optimization of the utilization of coffee farming production factors under pine stands. Data collection was conducted by interviewing 30 respondents who were selected by purposive random sampling. The data was analyzed using Cobb Douglas production function approach and Ordinary Least Square (OLS) method to estimate its parameters. To find out the optimal utilization of production factors, then the ratio of marginal production value (NPM) approach to production input prices is used. The results showed that the utilization of land production factors was not optimal because NPMXi/PXi = 3.237. While the seed, fertilizer, and labor factors were already inefficient with NPMXi/PXi value of -2.416, 0.066, and 0.480 respectively. Efforts to optimize income from coffee farming can still be turned out through expansion of planting areas if sufficient land is available or there is a reduction in the composition of coffee plants, the amount of fertilizer used, and the amount of excess labor.